Analysis of Axial Behavior in Cold-Formed Steel-Plywood Composite Walls - Saputra, Muhamad Dandy Harjunaseta Hadi; Siswosukarto, Suprapto; Awaludin, Ali (Journal of Engineering and Scientific Research, 2024)
The use of bricks as a wall material has significant drawbacks, including high weight and brittleness, making them vulnerable to damage, particularly under lateral loads like earthquakes. This study focuses on evaluating the axial performance of Cold-Formed Steel (CFS)-Plywood composite walls as an alternative to traditional brick walls. The study investigates the effects of bracing on axial compressive strength through laboratory testing of two composite wall specimens: one with bracing and one without. The results show that bracing significantly improves axial load capacity, with the braced specimen sustaining a maximum load of 69.666 kN, while the unbraced specimen withstood 64.413 kN. These findings highlight the potential of CFS-Plywood composite walls to serve as a lightweight, structurally sound alternative to brick walls, especially in multistory buildings subjected to axial loading.